Spent Fuel Performance Assessment and Research. - IAEA (International Atomic Energy Agency, 2021)
This publication is based on results obtained in the participating Member States during an IAEA coordinated research project (CRP) on spent fuel and storage system performance. It provides an overview of the technical issues related to wet and dry storage of spent fuel and summarizes the objectives and major findings of the research carried out within the framework of the CRP. The experience and insights provided by the participants are expected to assist readers in identifying challenges in implementing long term storage and promote understanding of the current status of spent fuel performance research.